2018
DOI: 10.1002/jso.25178
|View full text |Cite
|
Sign up to set email alerts
|

EC‐IC bypass for cerebral revascularization following skull base tumor resection: Current practices and innovations

Abstract: Complex skull base tumors can involve critical vessels of the head and neck. To achieve a gross total resection, vessel sacrifice may be necessary. In cases where vessel sacrifice will cause symptomatic cerebral ischemia, surgical revascularization is required. The purpose of this paper is to review cerebral revascularization for skull base tumors, the indications for these procedures, outcomes, advances, and future directions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…There were a few cases of skull base tumors requiring vessel revascularization. In a recent systematic review, Wolfswinskel et al showed that only about 368 cases of EC-IC bypass due to vessel injury for skull base tumors resection were reported from 1950 to 2018 [4]. According to Sekhar, there were 130 revascularization cases for tumors from 1988 to 2006 [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were a few cases of skull base tumors requiring vessel revascularization. In a recent systematic review, Wolfswinskel et al showed that only about 368 cases of EC-IC bypass due to vessel injury for skull base tumors resection were reported from 1950 to 2018 [4]. According to Sekhar, there were 130 revascularization cases for tumors from 1988 to 2006 [5].…”
Section: Discussionmentioning
confidence: 99%
“…Skull base tumors include pituitary tumors, sellar/parasellar tumors, meningioma, chordomas, chondrosarcomas, and squamous cell carcinoma… Most of the vessel revascularization cases were meningiomas [4]. This is because of the variety in their behaviors resulting in different vessel encasement.…”
Section: Discussionmentioning
confidence: 99%
“…In patients who would not tolerate ICA occlusion, adequate counselling on potential morbidity and mortality is mandatory and strategies such as endovascular flow diverter protective stenting or extracranial-to-intracranial bypass surgery should be considered when surgery can be staged or delayed while the patient undergoes double antiplatelet therapy (Fig. 4) 49,50 .…”
Section: Measures Against Major Vascular Complicationsmentioning
confidence: 99%
“…Diseases requiring deep field operations include: Cavernous malformations in the cerebral peduncles,[ 8 ] midbrain,[ 17 ] pons,[ 46 ] and other cavernomas of the brainstem[ 23 ] Arteriovenous malformations in the basal ganglia, thalamus,[ 27 ] choroid plexus,[ 13 ] brain stem,[ 18 ] and cerebellum[ 43 ] Complex aneurysms of the anterior inferior cerebellar artery,[ 24 ] posterior inferior cerebellar artery,[ 41 ] basilar artery,[ 26 ] and middle cerebral artery[ 20 ] Skull base tumors. [ 32 , 42 ] …”
Section: Introductionmentioning
confidence: 99%